Pengembangan Manajemen Skill pada Wirausaha Lokal: Studi Kasus UMKM Bu Umar Cake - Huda, Achmad Nuril; Hamdani, Umar; Rahayu, Wening Patmi; Winarno, Agung (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This paper provides a comprehensive examination of the concept and implementation of skill management as a cohesive set of competencies encompassing technical, interpersonal, conceptual, and strategic skills within organizational and entrepreneurial contexts. The background highlights the critical role of skill management in addressing the challenges posed by a highly competitive and rapidly evolving business environment, where mastery of these competencies determines both individual and organizational effectiveness in planning, organizing, leading, and controlling resources to achieve collective objectives. Grounded in a literature review of seminal works by Robbins & Coulter, Katz, Drucker, Mintzberg, Armstrong, and Barney & Hesterly, this study adopts a structured approach that covers definitions, classification of skill types, their roles in organizations, development strategies, implementation challenges, and applications in entrepreneurship. The findings indicate that: (1) technical, human, and conceptual skills are complementary across different managerial levels; (2) skill development requires a blend of formal education, field practice, mentorship, and technology utilization; (3) primary challenges include technological adaptation, complexity of decision-making, and limitations in training resources; and (4) in entrepreneurial ventures, effective skill management is fundamental to planning, finance, human resources, innovation, and communication. In conclusion, skill management should not be viewed as a static competency but as a strategic asset that must be continuously enhanced through lifelong learning, enabling both individuals and organizations to sustain growth and resilience in the era of globalization and digital transformation.